Bone marrow stromal cells derived exosomal miR-10a and miR-16 may be involved in progression of patients with multiple myeloma by regulating EPHA8 or IGF1R/CCND1. Issue 4 (29th January 2021) - Peng, Ye; Song, Xiaolu; Lan, Jianping; Wang, Xiaogang; Wang, Manling
Abstract : Abstract: Interaction with bone marrow stromal cells (BMSCs) has been suggested as an important mechanism for the progression of multiple myeloma (MM) cells, while exosomes are crucial mediators for cell-to-cell communication. The study was to investigate the miRNA profile changes in exosomes released by BMSCs of MM patients and explore their possible function roles. The microarray datasets of exosomal miRNAs in BMSCs were downloaded from the Gene Expression Omnibus database (GSE110271: 6 MM patients, 2 healthy donors; GSE78865: 4 donors and 2 MM patients; GSE39571: 7 MM patients and 4 controls). The differentially expressed miRNAs (DEMs) were identified using the LIMMA method. The target genes of DEMs were predicted by the miRwalk 2.0 database and the hub genes were screened by constructing the protein–protein interaction (PPI) network, module analysis and overlapping with the differentially expressed genes (DEGs) after overexpression or knockout of miRNAs. Three downregulated DEMs were found to distinguish MM from normal and MM-MGUS controls in the GSE39571 dataset; one downregulated and one upregulated DEMs (hsa-miR-10a) could differentiate MM from normal and MM-MGUS controls in the GSE110271-GSE78865 merged dataset. Furthermore, 11 downregulated (hsa-miR-16) and 1 upregulated DEMs were shared between GSE39571 and merged dataset when comparing MM with normal samples. The target genes were predicted for these 17 DEMs. PPI with module analysis showed IGF1R and CCND1 were hub genes and regulated by hsa-miR-16. Furthermore, EPHA8 was identified as a DEG that was downregulated in MM cells when the use of has-miR-10a mimics; while IGF1R, CCND1, CUL3, and ELAVL1 were also screened as DEGs that were upregulated in MM cells when silencing of hsa-miR-16. BMSCs-derived exosomal miR-10a and miR-16 may be involved in MM progression by regulating EPHA8 or IGF1R/CCND1/CUL3/ELAVL1, respectively. These exosomal miRNAs or genes may represent potential biomarkers for diagnosis of MM and prediction of progression and targets for developing therapeutic drugs. Abstract : Supplemental Digital Content is available in the text